Desenvolvimento e caracterização de biscoitos elaborados com farinha mista de arroz vermelho e feijão carioca - Magalhaes, Camila Soares de (2018)
Red rice is a cereal with superior nutritional quality compared to white rice due the higher levels of fiber, vitamins, minerals and phenolic compounds. Beans are the most important legume for human diet and Carioca variety is the most consumed by Brazilians. It is a source of energy, proteins, vitamins and minerals. Carioca beans, BRS Cometa variety (part of Rede Bio-Fort biofortification program, Embrapa) show high iron and zinc levels. The rice and beans combination increase meal protein quality, and has nutritional, economic and social importance for Brazilians. Rice and beans in the form of flours improve cookie the nutritional quality, besides of serving as an option for celiac people. The aim of this work was to develop and characterize cookies made of mixed red rice (Oriza sativa L.) and carioca beans BRS Cometa (Phaseolus vulgaris L.) A second-order rotational composite design was used to study the effects of different concentrations of carioca bean (CB) (14.65 g / 85.35 g / 100 g) on red rice (RR) and margarine (12.06 to 20.54 g / 100 g) on total formulation. The variables studied were measurements, water activity (aw), color, texture, sensory analysis, bioactive compounds, nutritional composition, electrophoresis, storage and scanning electron microscopy (SEM). CB replacement up to 85.35 g / 100 g reduced the diameter, specific volume and influenced the expansion factor, while the addition of margarine in the formulation up to 20.54 g / 100 g increased expansion factor of cookies. Aw was below 0.53, within the limit for this kind of product. Cookies showed dark, intense and reddish coloration. CB increased cookie hardness, while margarine turned cookies softer. The addition of CB up to 50 g / 100 g was well accepted sensorially and the higher the amount of margarine was, the greater were grades for acceptance, texture and flavor attributes. CB concentration directly increased moisture, ashes, proteins, iron, zinc and fibers, and had the opposite effect on total carbohydrates. Margarine reduced cookies total carbohydrates but increased amount of lipids and energy value. Processing RR and CB flour reduced the total phenolic compounds content and antioxidant activity in both flours, but only decreased the tannins in CB. CB increased total phenolic compounds and tannins concentration in cookies. In relation to the Electrophoresis, CB flour processing reduced globulins and phytohemoglobulins protein fraction saturation. Raw and processed RR presented similar protein saturations, with the presence of albumin, glutenin, globulin and prolamin. Cookies showed weaker protein bands in relation to the flours, possibly by the addition of other non-protein ingredients. Cookies were stable during the 60 days of storage. Through SEM It was possible to observe that cookies were in general homogeneous but presenting some protuberances, due to the amid-lipid complex. Finally, this study showed the possibility to make cookies with mixed RR and CB flours. CB up to 50g / 100g and 13,3 g to 16,3 g / 100 g of margarine presented good sensory, nutritional and technological characteristics. So, more nutritious products can be offered to the market to contribute to healthier diet.